Cryotolerance of apple tree bud is independent of endodormancy - Bilavcik, Alois; Zamecnik, Jiri; Faltus, Milos (Frontiers in Plant Science, 2015)
Increasing interest in cryopreservation of dormant buds reveals the need for better understanding of the role of dormancy in cryotolerance. Dormancy stage and low temperature survival of vegetative apple buds (Malus domestica Borkh.), cultivars “Sampion” and “Spartan”, collected from orchard were evaluated during three seasons contrasting in temperature and precipitation throughout the arrested plant growth period. During each season, the cultivars differed either in the onset of the endodormancy or in the length of the endodormant period. A simple relation between endodormancy of the buds and their water content was not detected. The cryosurvival of vegetative apple buds of both cultivars correlated with their cold hardening without direct regard to their particular phase of dormancy. The period of the highest bud cryotolerance after low temperature exposure overlapped with the endodormant period in some evaluated seasons. Both cultivars had the highest cryosurvival in December and January. The presented data were compared with our previous results from a dormancy study of in vitro apple culture. Endodormancy coincided with the period of successful cryosurvival of apple buds after liquid nitrogen exposure, but as such it was not decisive for their survival and did not limit their successful cryopreservation.